Pengaruh Program Adiwiyata Terhadap Pengetahuan Perilaku dan Keterampilan Siswa dan Guru dalam Mengelola Lingkungan pada SMK di Kabupaten Pelalawan - Syoffnelli, Syoffnelli; Saam, Zulfan; Thamrin, Thamrin (Universitas Riau, 2016)
Abstrak: The study aimed to determine adiwiyata program effects on knowledge, behaviour and skills of students and teachers also compared schools that have implemented the adiwiyata program with schools that have not implemented adiwiyata program. This study is a quantitative descriptive research. The subjects were students and teachers of SMK Negeri 1 Pangkalan Kerinci and SMK Negeri 1 Bunut with total 194 people. The data collection methode used were questionnaires, interviews and observations, data analysis technique using Chi-square test with SPSS version 20 for windows. Results of the study Chi Square test showed between SMK 1 Pangkalan Kerinci with SMKN 1 Bunut about students' knowledge Chi Square count 140.437 and Chi Square table 101.879, student behavior Chi Square count 102.920 and Chi Square tables 101.879 and attitudes Chi Square count 101 994 and Chi Square tables 101.879. Knowledge, attitudes and skills of teachers Chi Square test results Chi Square count of 10,000 and Chi Square Table 18.307. It can be concluded that the existence of a significant difference of knowledge, attitudes and skills of students between SMK 1 Pangkalan Kerinci with SMKN 1 Bunut, because the value of Chi Square count is greater than the value of Chi Square table and there was no significant difference about knowledge, attitudes and skills teacher between SMKN 1 Pangkalan Kerinci with SMKN 1 Bunut, because there is a calculated value of Chi Square is smaller than the value of Chi Square table.